Life Crafting as a Way to Find Purpose and Meaning in Life - Schippers, Michaéla C.; Ziegler, Niklas (Frontiers in Psychology, 2019)
Having a purpose in life is one of the most fundamental human needs. However, for most people, finding their purpose in life is not obvious. Modern life has a way of distracting people from their true goals and many people find it hard to define their purpose in life. Especially at younger ages, people are searching for meaning in life, but this has been found to be unrelated to actually finding meaning. Oftentimes, people experience pressure to have a “perfect” life and show the world how well they are doing, instead of following up on their deep-felt values and passions. Consequently, people may need a more structured way of finding meaning, e.g., via an intervention. In this paper, we discuss evidence-based ways of finding purpose, via a process that we call “life crafting.” This process fits within positive psychology and the salutogenesis framework – an approach focusing on factors that support human health and well-being, instead of factors that cause disease. This process ideally starts with an intervention that entails a combination of reflecting on one’s values, passions and goals, best possible self, goal attainment plans, and other positive psychology intervention techniques. Important elements of such an intervention are: (1) discovering values and passion, (2) reflecting on current and desired competencies and habits, (3) reflecting on present and future social life, (4) reflecting on a possible future career, (5) writing about the ideal future, (6) writing down specific goal attainment and “if-then” plans, and (7) making public commitments to the goals set. Prior research has shown that personal goal setting and goal attainment plans help people gain a direction or a sense of purpose in life. Research findings from the field of positive psychology, such as salutogenesis, implementation intentions, value congruence, broaden-and-build, and goal-setting literature, can help in building a comprehensive evidence-based life-crafting intervention. This intervention can aid individuals to find a purpose in life, while at the same time ensuring that they make concrete plans to work toward this purpose. The idea is that life crafting enables individuals to take control of their life in order to optimize performance and happiness.